1995
DOI: 10.1029/95ja00063
|View full text |Cite
|
Sign up to set email alerts
|

Density depletions at the 10‐m scale induced by the Arecibo heater

Abstract: In June 1992 a NASA sponsored sounding rocket was flown through the Arecibo heater beam to study the structure of the heated volume. The rocket carried an instrument payload and traversed the 5.1-MHz reflection height at 268.5 kin. Data from the plasma density probe are presented in this paper. The rocket passed through several regions of disturbed plasma both above and below the reflection level. In these regions, over 180 deep filamentary density depletions were detected. Measured perpendicular to the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
118
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 31 publications
19
118
0
1
Order By: Relevance
“…Further radar backscatter measurements established the field-transverse wave number spectrum of the irregularities (Minkoff, 1974). These observations have been confirmed by in-situ rocket measurements (Kelley et al, 1995;Franz et al, 1999). The spectrum is essentially flat with increasing wave number up to a first "break-point" at scales of a few metres to tens of metres when an inverse power-law dependence takes over.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Further radar backscatter measurements established the field-transverse wave number spectrum of the irregularities (Minkoff, 1974). These observations have been confirmed by in-situ rocket measurements (Kelley et al, 1995;Franz et al, 1999). The spectrum is essentially flat with increasing wave number up to a first "break-point" at scales of a few metres to tens of metres when an inverse power-law dependence takes over.…”
Section: Introductionsupporting
confidence: 52%
“…Such theories do not take into account the possible effects on plasma transport due to the excitation of plasma turbulence in the region where the pump wave interacts with the plasma. In addition, the small-scale irregularities involve steep gradients in plasma density which may be unstable to, for example, the drift-wave instability, as has been suggested by Kelley et al (1995). Such instabilities could prevent striations reaching the stationary state, as predicted by current theories.…”
Section: Introductionmentioning
confidence: 85%
“…Although it is not readily apparent from this linear plot, the filaments in all three patches have similar relative depletions between 3% and 10%. Their mean width at half maximum is 15 m, and the spacing between filaments across the magnetic field is roughly 45 m. We found no obvious correlation between the width of a filament and its depletion depth [Kelley et al, 1995]. Figure 2 is the one-dimensional wavenumber spectrum computed from the Langmuir probe time series.…”
Section: Scattering Calculationmentioning
confidence: 99%
“…This agrees with a vast set of experimental and theoretical studies [see Robinson, 1989] that concluded that the filaments are highly field aligned. The elongation ratio of the filaments is likely to be •20,000 since meter-scale gradients were detected in all three patches [Kelley et al, 1995].…”
Section: Scattering Calculationmentioning
confidence: 99%
“…Plasma irregularities set in within $10 s of pumping [Utlaut et al, 1970] and self-focusing of the pump wave in the magnetic zenith can occur for small plasma depletions of order <1% [Georges, 1970]. Rocket and satellite measurements at Arecibo of pump-induced striations revealed smallscale plasma depletions up to 12% (mean 6%) [Kelley et al, 1995] and 3% [Farley et al, 1983], respectively, for low latitudes. Rocket measurements at EISCAT show smallscale pump-induced plasma depletions up to 2% (typically <1%) [Rose et al, 1985] for high latitudes.…”
Section: Introductionmentioning
confidence: 99%